2014
DOI: 10.1038/ismej.2014.166
|View full text |Cite
|
Sign up to set email alerts
|

Catchment-scale biogeography of riverine bacterioplankton

Abstract: Lotic ecosystems such as rivers and streams are unique in that they represent a continuum of both space and time during the transition from headwaters to the river mouth. As microbes have very different controls over their ecology, distribution and dispersion compared with macrobiota, we wished to explore biogeographical patterns within a river catchment and uncover the major drivers structuring bacterioplankton communities. Water samples collected across the River Thames Basin, UK, covering the transition fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
181
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(208 citation statements)
references
References 65 publications
25
181
1
1
Order By: Relevance
“…Our study thus paves the way toward new mechanistic understanding of microbial diversity patterns in streams, and further supports the notion that microorganisms exhibit distributional patterns along the fluvial continuum (Besemer et al, 2013;Read et al, 2014;Savio et al, 2014) as recognised for invertebrates (Vannote et al, 1980). These findings may have broader impacts as the treeline moves upwards because of climate warming in the Alps.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Our study thus paves the way toward new mechanistic understanding of microbial diversity patterns in streams, and further supports the notion that microorganisms exhibit distributional patterns along the fluvial continuum (Besemer et al, 2013;Read et al, 2014;Savio et al, 2014) as recognised for invertebrates (Vannote et al, 1980). These findings may have broader impacts as the treeline moves upwards because of climate warming in the Alps.…”
Section: Discussionsupporting
confidence: 53%
“…The relationships between downstream shifts in resources (i.e., primarily autochthonous sources upstream versus more allochthonous sources downstream), hydrogeomorphology and biotic communities have been described by the River Continuum Concept (Vannote et al, 1980). Microorganisms were not encapsulated in the River Continuum Concept, and yet evidence increasingly suggests that microbial communities predictably change along the river continuum (Besemer et al, 2013;Read et al, 2014;Savio et al, 2014). However, the potential drivers of these patterns remain poorly understood, which is noticeable, given the relevance of microorganisms for stream ecosystem functions (Battin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cytophaga-Flavobacteria were not found in this study, in contrast with many studies where Bacteroidetes have been found to be a frequent component of the riverine bacterial community (Crump et al 2009;Read et al 2015) or the main group forming filamentous cells under high grazing pressure (Salcher et al 2005). On the contrary, other studies (Puddu et al 2003;Crespo et al 2013) have demonstrated that Cytophaga-Flavobacteria are usually enriched on particulate organic detritus, and they could be specialists for particulate organic matter degradation, which was removed by filtration in this experiment.…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast, there was a higher proportion of LNA bacteria found in the coastal Canet lagoon (57%; Servais et al 2003), eastern Mediterranean Sea (65%), North Atlantic (64%; Li et al 1995) and the Gulf of Mexico (62%; Jochem et al 2004). In comparison, only a few reports are available on LNA and HNA bacteria in freshwater environments (Ni et al 2015;Read et al 2015). For example, Joux and colleagues investigated the percentages of LNA and HNA bacteria and the effect of salinity and chlorophyll-a on those two groups along the Rhone River (France) (Joux et al 2005).…”
Section: Introductionmentioning
confidence: 84%
“…Wang and colleagues isolated three typical pure cultures of LNA that were closely affiliated to Polynucleobacter from freshwater environments in Switzerland (Wang et al 2009). To the best of our knowledge, field data on the spatial distribution patterns of LNA and HNA fractions are very scarce in freshwater environments (Ni et al 2015;Read et al 2015), and there is no information concerning the changes in cytometric characteristics of LNA and HNA bacteria on a large river-catchment scale. In the current study, we profiled the relationship between the cytometric characteristics of LNA and HNA bacteria, illustrated the biogeographical patterns (i.e.…”
Section: Introductionmentioning
confidence: 99%